O boto-cinza (Sotalia guianensis) no estuário dos rios Piraquê-Açu e Piraquê-Mirim, sudeste do Brasil : ocorrência, uso do habitat, padrão comportamental e percepção da comunidade tradicional - Bicalho, Aldo Marcello Costa (2018)
Guiana dolphin (Sotalia guianensis) is a small cetacean, widely distributed and endemic to the tropical and subtropical Atlantic Ocean, being easily observed in the coastal and estuarine regions. The information related to this specie in Brazilian waters is scarce and punctual, being considered in a situation of vulnerability to the conservation of its populations. This study was aimed at investigating the ecology of the Guiana dolphin in the estuary of Piraquê-Açu and Piraquê-Mirim rivers, Aracruz, ES. The presence of the Guiana dolphin in the estuary was employed using three methodologies: monitoring through fixed point and through cruises and ethnographic interviews with local community. Fixed-point monitoring was performed weekly at two sampling points, lasting five hours daily per point, between April 2016 and May 2017. Cruises monitoring were performed monthly at six sampling points, each lasting five hours between July 2016 and July 2017. Moreover, the environmental parameters (hydrogen-ionic potential, surface temperature of water, dissolved oxygen, salinity, turbidity, wind speed, precipitation, type, level and direction of tides) were evaluated in both points of the monitoring by fixed point and of the cruises monitoring. Ethnographic interviews were carried out with 30 artisanal fishermen who work in the north coast of Espírito Santo and with 30 crabmen catchers who work in the region of Aracruz. The occurrence of Guiana dolphin was verified in the estuary and presented a seasonal variation, with greater presence of the specie in spring and summer. The entrance to the estuary was favored by the flood tide and the preferential use of the habitat was for travelling and foraging. No correlation was verified between the analyzed parameters and the occurrence of the specie in the estuarine environment, except for wind speed. The local ecological knowledge of artisanal fishermen and crab catchers regarding Guiana dolphin corroborates with those described in the literature and with those observed during the monitoring carried out in this research and add important information to scientific knowledge about the specie. The local community's positive insight regarding Guiana dolphin represents an important tool for management and conservation proposals of the specie in the region.